The rescue - Sparks, Nicholas (New York, NY : Grand Central Publishing, 2011)
Reluctant to take chances in the world of romance, volunteer firefighter Taylor McAden experiences a dramatic change of heart after a near-fatal automobile accident leads to a fateful encounter with Denise Holden.
Reprint. Originally published: 2000.
Keywords: American fiction; Single mothers -- Fiction